Implementasi SOP Account Payable Pada Pelaporan Penerimaan Barang di Vasa Hotel Surabaya - Angelita Kracibaya Nauli Panggabean (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to analyze the implementation of Standard Operating Procedures (SOP) for accounts payable in reporting goods receipts at the Vasa Hotel Surabaya. Quantitative methods are used with data collection techniques through observation, interviews and document analysis. The research results show that the implementation of SOP accounts payable still faces several challenges, especially in terms of completeness of Receiving Report documents and coordination between departments. This research provides recommendations for improving process efficiency and compliance with existing SOPs.